2020
DOI: 10.31186/jipi.22.1.9-15
|View full text |Cite
|
Sign up to set email alerts
|

UJI KONSENTRASI CENDAWAN Beauveria bassiana (Bals.) Vuill TERHADAP MORTALITAS KEPIK POLONG (Riptortus linearis) F. PADA TANAMAN KEDELAI

Abstract: [TESTING THE CONCENTRATION OF FUNGI Beauveria bassiana (Bals.) ON MORTALITY OF POD BORER (Riptortus linearis F.) ON SOYBEAN]. To control pod borer (Riptortus linearis F). on soybean using chemical insecticides can cause pollution to the environment, kill non-targeted insects and evolve pest resistance. The use of entomopathogenic fungus is an environmentally friendly alternative, one of which is Beauveria bassiana. (Bals.). The purpose of this study was to obtain an effective concentration of Beauveria bassian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
0
0
1
Order By: Relevance
“…Therefore, an investigation on the potential entomopathogenic fungi has been carried out to control R. linearis. A previous study reported the highest potential from Lecanicillium lecanii in controlling R. lienaris in comparison to Beauveria bassiana (Riningrum et al 2020) and Metarhizium (Astuti et al 2020).…”
Section: Introductionmentioning
confidence: 93%
“…Therefore, an investigation on the potential entomopathogenic fungi has been carried out to control R. linearis. A previous study reported the highest potential from Lecanicillium lecanii in controlling R. lienaris in comparison to Beauveria bassiana (Riningrum et al 2020) and Metarhizium (Astuti et al 2020).…”
Section: Introductionmentioning
confidence: 93%
“…Kematian larva terjadi sejak hari ke-3 HSA dan terus mengalami peningkatan hingga hari ke-7 HSA. Waktu kematian yang dibutuhkan oleh jamur B. bassiana dalam menginfeksi serangga uji adalah sekitar 2-4 hari (Riningrum et al, 2020). Perlakuan jamur B. bassiana yang tumbuh pada pH 5,5 dan suhu 28°C memiliki kemampuan dalam membunuh larva S. litura tertinggi (76,67%), kemudian disusul pada perlakuan jamur B. bassiana yang tumbuh pada pH 8 dan suhu 28°C (63,33%) dan yang terendah pada perlakuan jamur B. bassiana yang tumbuh pada pH 5,5 dan suhu 24°C (60%).…”
Section: Pengaruh Tingkat Keasaman Media Dan Suhu Penyimpanan Terhada...unclassified